Причини поразки ЗУНР: вторгнення, бездіяльність чи зрада? - Якимович, Б. (Український історичний журнал, 2019)
Оцінюючи Українську революцію 1917–1921 рр. та утворення ЗУНР другим феноменом в історії нашого народу після постання козацької держави під проводом Б.Хмельницького у XVII ст., автор звертає особливу увагу на помилки політичного та військового проводів галичан, які призвели до падіння державності в Галицько-Буковинсько-Закарпатському краї. Обґрунтовано часові відтинки, коли тричі була можливість вигнати польських загарбників із території Східної Галичини. Саме втрачений час, дезорієнтація у внутрішньопольських суперечностях, дезорганізація запілля, нереалізація Акта злуки між ЗУНР та УНР, події на Наддніпрянщині зумовили падіння Західноукраїнської Народної Республіки, котра вже у другій чверті 1919 р. опинилася сам на сам із відтвореною Польщею. Якраз тоді Антанта за нейтральної позиції США значними силами й засобами підтримала поляків, тож українці виявилися між Польщею, Румунією, російськими білими та червоними. Assessing the Ukrainian Revolution of 1917–1921 and the establishing of the West Ukrainian People’s Republic as the second most important phenomenon in the history of the Ukrainian people after the establishment of the Cossack State under the leadership of B.Khmelnytskyi in the 17th century, the author of the present study pays a special attention to the mistakes of the political and army leadership of the people of Halychyna, which caused the demise of the state in the Halychyna- Bukovyna-Zakarpattia region. The author identifies three time periods, during which it was possible to send the Polish occupiers away from the territory of Eastern Halychyna. It was the wasted time, disorientation in the Polish domestic contradictions, disarrangement of the rear, failure to enforce the Reunion Act of the WUPR and the Ukrainian People’s Republic, as well as the developments in the Naddniprianshchyna region caused the demise of the WUPR. The latter found itself face to face with the might of the revived Polish state already in the second quarter of 1919. Just at that time the Entente, with a neutral position of the United States, supplied the Poles with considerable forces and means throwing the Ukrainians at the paws of Poland, Romania, and White and Red Russia.